Effects of Solar Proton Events Associated With X-Ray Flares on Near-Earth Electron and Proton Fluxes Based on ZH-1 Satellite Observations - Wang, Lu; Zhang, Zhenxia; Shen, Xunhui; Li, Xinqiao; Liang, Xiaohua; Zhima, Zeren; Chu, Wei; Guo, Feng; Zhou, Na; Chen, Huaran; Wei, Daihui (Frontiers in Earth Science, 2022)
Solar eruptions can cause violent effects on the space environment. Electromagnetic radiation from solar flares will be the first to arrive on the earth at the speed of light, followed by solar energetic charged particles.The last to appear will be coronal mass ejections and geomagnetic storm. Based on observations of ZH-1 satellite, we report several strong disturbed space environment events, all of them with solar proton events (SPEs), and analyze the driven mechanisms: 1) On November 29, 2020, an M4.4 flare accompanied with a full halo CME caused a gradual SPE, which was mainly driven by CME shocks. 2) On May 28, 2021, a C9.4 flare brought an impulsive SPE, which was accelerated by the flare. The heliolongitude of this small flare was 63W°, near the footpoint of the magnetic field line leading from the sun to the earth. 3) On October 28, 2021, a full-halo CME accompanied with an X1.1 flare brought a gradual SPE.On November 2, 2021, another fast full halo CME accompanied with flare was ejected. The faster CME of November 2 caught up and swept up the slower CME of November 1, and subsequently caused a severe geomagnetic storm (minimum Dst = -101) and a high-energy electron storm on November 4 . The observations of the above three space environmental events confirm that the data quality of the high-energy particle package (HEPP) from ZH-1 are highly reliable and accurate, and is higly advantageous to monitor the variation of energetic particles and X-ray in the radiation belt of the earth during solar activities.